Beta-2 Microglobulin in Whole Unstimulated Saliva Can Effectively Distinguish Between Sjögren’s Syndrome and Non-Autoimmune Sicca Symptoms - Janett RIEGA-TORRES,; Guillermo DELGADO-GARCÍA,; Julio César SALAS-ALANÍS,; Cassandra SKINNER-TAYLOR,; Lorena PÉREZ-BARBOSA,; Mario GARZA-ELIZONDO,; Celia Nohemí SÁNCHEZ-DOMÍNGUEZ,; Luis Ángel CECEÑAS-FALCÓN,; Karim MOHAMED-NORIEGA,; Jesús MOHAMED-HAMSHO,; David VEGA-MORALES, (Archives of Rheumatology, 2017)
Objectives: This study aims to describe salivary beta-2 microglobulin (sB2M) levels in our setting and to assess the performance of sB2M for the diagnosis of Sjögren's syndrome (SS). Patients and methods: This cross-sectional, comparative study included 192 SS patients (2 males, 190 females; mean age 53.1 years; range 23 to 84 years) and 64 healthy controls (1 male, 63 females; mean age 46.9 years; range 21 to 82 years). Patients were divided into three groups as those with primary SS, secondary SS, and sicca non-Sjögren's syndrome (snSS). sB2M was measured by enzyme-linked immunosorbent assay in whole unstimulated saliva (ng/mL). Differences in sB2M were evaluated using the Kruskal-Wallis test. Receiver operating curves were generated to determine the performance of sB2M for distinguishing between SS and non-autoimmune snSS groups, and between SS group and healthy controls. Results: The primary SS and secondary SS groups had a significantly higher concentration of sB2M than the other two groups. There was no significant difference in the concentration of sB2M between primary SS and secondary SS groups, and neither between snSS group and healthy controls. The receiver operating curve analysis for distinguishing SS and snSS showed an area under the curve of 0.661 (95% confidence interval 0.590-0.728, p=0.0001) with an optimal cutoff value of 0.582 ng/mL. Sensitivity, specificity, positive predictive value, and negative predictive value were 68.7%, 59.3%, 20.2%, and 92.7%, respectively. The reported prevalence of SS in Mexico was considered when calculating the last two values. Conclusion: In our setting, sB2M effectively distinguished between SS patients and non-autoimmune sicca symptoms. Including sB2M in our conventional diagnostic arsenal may assist in the evaluation of patients in whom SS is suspected; however, further studies are needed to clarify this hypothesis.